Serum NR1 and NR2 concentrations in first-episode schizophrenia and clinical high-risk for psychosis - Zhen Mao; Feng Li; Lige Ge; Wenpeng Hou; Yushen Ding; Feifei Wang; Yujie Wen; Xueqi Wang; Yongying Cheng; Weiwei Hou; Lu Wang; Xinke Shi; et al. (BMC Psychiatry)
Abstract Background This study evaluated the utility of serum NR1 and NR2 concentrations in identifying individuals with first-episode schizophrenia (FES) and clinical high risk (CHR) as well as their correlations with clinical symptoms and cognitive domains. Methods This cross-sectional study compared peripheral blood NR1 and NR2 concentrations among the FES, CHR, and healthy control (HC) groups and examined their association with cognitive function. Serum concentrations of NR1 and NR2 subunits were measured using ELISA, and cognitive function was assessed using the MATRICS Consensus Cognitive Battery. Concentrations were compared among groups using the analysis of covariance or non-parametric tests and ROC curve analysis, and correlation was determined using the Pearson or Spearman method. Results A total of 41 FES cases, 34 CHR cases, and 41 HC were included in the study. Serum NR1 concentrations significantly varied among the three groups (Z = 16.19, P < 0.001) and were significantly different between the FES group and the CHR (Z = -4.04, P < 0.001) and HC groups (Z = -2.49, P = 0.01). Additionally, serum NR2 concentration was significantly different between the CHR and HC groups (F = 5.37, P = 0.02). In the FES group, serum NR1 concentration was negatively correlated with speed of processing (r = -0.41, P = 0.02), whereas serum NR2 concentration was negatively correlated with verbal learning (r = -0.40, P = 0.02). In the CHR group, serum NR1 concentration was positively correlated with the total MCCB score (r = 0.40, P = 0.04). ROC curve analysis showed that NR2 level was better for discriminating FES (AUC: 69%; sensitivity: 56%; specificity: 85%; optimal cutoff value: 32.80 ng/mL) and CHR (AUC: 74%; sensitivity: 62%; specificity: 85%; optimal cutoff value: 32.77 ng/mL). Conclusions Serum NR1 and NR2 concentrations show potential for early identification of individuals with psychosis, but further validation is needed, and they are also correlated with cognition. Furthermore, serum NR2 concentration is more stable and serves as a promising objective biomarker for quantitative assessment.